2020
DOI: 10.3390/insects11080512
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dynamics of the Alien Invasive Insect Pest Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) in Manica Province, Central Mozambique

Abstract: The alien invasive insect pest Spodoptera frugiperda Smith (Lepidoptera: Noctuidae), commonly referred to as fall armyworm (FAW), is causing significant losses to maize production in Africa since its detection in 2016. Despite being the primary insect pest of the main food crop in the country, researchers have concentrated their efforts on methods of control, and there are no published studies on its seasonality which could assist farmers in delivering effective methods of control in periods of heavy infestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…This can be explained by the fact that in this interval, maize planted from October to December is still in the vegetative stage which is the most preferred by FAW. But a field survey conducted from May to August 2019 and between December 2019 and January 2020 in the same area, found that FAW infestation was higher during the dry season (Caniço et al 2020).…”
Section: Discussionmentioning
confidence: 92%
“…This can be explained by the fact that in this interval, maize planted from October to December is still in the vegetative stage which is the most preferred by FAW. But a field survey conducted from May to August 2019 and between December 2019 and January 2020 in the same area, found that FAW infestation was higher during the dry season (Caniço et al 2020).…”
Section: Discussionmentioning
confidence: 92%
“…In a study conducted by Midega et al [49] in Kenya, Uganda, and Tanzania, the team reported 82.7% and 86.7% reduction in larvae per plant and plant damage, respectively in climate-adapted push-pull compared to maize monocrop plots, and a resultant 2.7-fold higher grain yield in the climate-adapted push-pull plots (Figure 6). There was a similar finding in Uganda, where maize yield from climateadapted PPT was significantly greater compared with maize intercropped with edible legumes or mono-cropped maize [48].…”
Section: Push-pull Technologymentioning
confidence: 98%
“…Successful agroecological management is based on the understanding of key principles such as complex interactions within the ecosystem and contextualized solutions to local problems [47]. Agroecological management practices to reduce FAW populations in Africa include cultural and mechanical control, intercropping, crop rotation with non-host crop, weed management and intercropping maize with the moth repellant Greenleaf desmodium ("Push") with Brachiaria cv Mulato planted around the intercrop ("Pull") [47][48][49].…”
Section: Agroecological Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…S. frugiperda is particularly serious because of frequent population outbreaks in corn (maize), soybean, and cotton crops 1 , 2 , 5 , 6 . Spodoptera frugiperda was first reported in Africa in 2016 and subsequently in Asia and Oceania, and has become a serious cosmopolitan pest of corn, rice and other cereal crops 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%